A case of envenomation by neotropical Opisthoglyphous snake Thamnodynastes pallidus (Linnaeus, 1758) (Colubridae: Dipsadinae: Tachymenini) in Brazil - Araújo, Paula F. de (2018)
This is a case report of a bite by an Opisthoglyphous snake Thamnodynastes pallidus (Linnaeus, 1758) in an undergraduate herpetologist observed at the Universidade Federal da Paraiba (Rio Tinto, PB, Brazil). The female victim was bitten in her left hand between the index finger and the middle finger and presented symptoms of local envenomation such as bleeding, itching, pain in the wound and swelling. The patient was first seen at the University and afterwards at home during the 36 hours following the incident, when the symptoms disappeared. This is the first case report of an accident by T. pallidus in a human being in Brazil.